Does gender make a difference? Seatbelt use and the risk of severe injuries among drivers hospitalized in Level-1 trauma centers. (December 2021) - Cohen-Manheim, Irit; Goldman, Sharon; Radomislensky, Irina; Givon, Adi; Peleg, Kobi; Bodas, Moran; ,; Acker, A.; Aviran, N.; Bahouth, H.; Bar, A.; Becker, A.; et al.
Abstract: Background: A considerable proportion of hospitalized trauma patients are due to motor vehicle crashes. While the safety implications of seatbelt use in reducing severe injuries and fatalities are well established, and while it is argued that females are underrepresented in safety vehicle tests, it is unclear whether seatbelts have equally benefitted drivers of either gender. Previous studies have not, to the best of our knowledge, tested moderation effect of seatbelt use on the association between gender and crash-related injury. Methods: We performed a retrospective cohort study using data drawn from the National Trauma Registry database, 2008–2018, to determine the role of car driver's gender as a predictor of injury outcome following a road traffic crash resulting in hospitalization. Modified Poisson regression models were applied controlling for age, ethnicity, seatbelt use, impact type, road type, and year of hospitalization. Effect modification of the gender-injury outcome associations was tested for belt-restraint status using multiplicative interaction terms. Results: There was no evidence for a modification effect of the gender-seatbelt and injury associations, indicating that males are at greater risk for injury, independent of seatbelt use. The relative risk (RR) for a male driver to sustain severe injuries was approximately two fold the injury risk of female drivers (RR = 1.9, 95%CI: 1.6–21). The corresponding RRs for severe head and torso injuries were 2.5 (95%CI: 2.0–3.2) and 1.8 (95%CI: 1.5–2.2), respectively. Conclusions: The results suggest that seatbelts provide equal injury protection for drivers of both genders; yet, males are at a greater risk to sustain severe injuries regardless of seatbelt use. This finding points to the possibility that risk-taking behaviors contribute to gender specific disparities and should be the focus of targeted interventions by health professionals and policymakers. Highlights: Seatbelts provide equal injury protection for private car drivers of either gender. Yet, males are at a greater risk to sustain severe injuries regardless of seatbelt use. Risk-taking behavior is a possible target for addressing this gender-specific disparity.